Bioeconomics Of Culture For Common Carp In Floating Net Cages In The Maninjau Lake West Sumatra - Mohammad Noor (Universitas Islam Indonesia, 2002)
This study was conducted in Maninjau Lake, West Sumatera from April 1998 to Febru¬ary 1999. The objective of this study is: (1) to estimate the relation between aquaculture of production and its biological performance, economics as well as physical system, (2) to know which inputs are most important determinants of total output, (3) to identify the level of input efficiency. Data were collected by RRA and Survey using Semi-Structure Interview methods, and also from record keeping form of producers. The unconstrained Cobb Douglass production function was applied to estimate its relationship, and 8 explanatory variables con¬sist of biological inputs, economical inputs and physical inputs were hypothesized to explain the production yields. This study shows that F-value and R2 or coefficient of determination were highly significant of the 8 independent variables, only 5 variables have the expected positive sign and rest of them result negative sign. T- test shows that 6 explanatory variables are significant in explain during the output. The highest contribution and the most important deter¬minants of the total output are specific growth rate of biomass, stocking density and feed. The inputs of specific growth rate of biomas, stocking density and feeding labor for the fish fed should be increased to maximize profit, while reducing other inputs. Keywords: Bioeconomics, common carp, gloating net cage, Maninjau Lake.